Identification of a Novel MLPH Missense Mutation in a Chinese Griscelli Syndrome 3 Patient - Huang, Qiaorong; Yuan, Yefeng; Gong, Juanjuan; Zhang, Tianjiao; Qi, Zhan; Yang, Xiumin; Li, Wei; Wei, Aihua (Frontiers in Medicine, 2022)
Melanophilin (MLPH) functions as a linker between RAB27A and myosin Va (MYO5A) in regulating skin pigmentation during the melanosome transport process. The MYO5A-MLPH-RAB27A ternary protein complex is required for anchoring mature melanosomes in the peripheral actin filaments of melanocytes for subsequent transfer to adjacent keratinocytes. Griscelli syndrome type 3 (GS3) is caused by mutations in the MLPH gene. So far, only five variants of MLPH associated with GS3 have been reported. Here, we reported the first patient with GS3 in a Chinese population. The proband carried a novel homozygous missense mutation (c.73G>C; p.D25H), residing in the conserved Slp homology domain of MLPH, and presented with hypopigmentation of the hair, eyebrows, and eyelashes. Light microscopy revealed the presence of abnormal pigment clumping in his hair shaft. In silico tools predicted this MLPH variant to be likely pathogenic. Using immunoblotting and immunofluorescence analysis, we demonstrated that the MLPH (D25H) variant had an inhibitory effect on melanosome transport by exhibiting perinuclear melanosome aggregation in melanocytes, and greatly reduced its binding to RAB27A, although the protein level of MLPH in the patient was not changed. Our findings suggest that MLPH (D25H) is a pathogenic variant that expands the genetic spectrum of the MLPH gene.